O incremento da mobilidade internacional com contrato local e as políticas e práticas da área de recursos humanos - Lima, Daniela Farah de (2018)
In view of the need for global action, professionals need to present flexibility in international mobility, in this research understood as the performance of the worker in a country other than his or her country of origin. Seven types of international mobility are highlighted: expatriation, flexpatriation, cross-border movement, short-term assignment, inpatriation, migration and self-initiated expatriation - more specifically, the modality with local contract, object of this study. This research has as theme the increase of the international mobility with local contract and the policies and practices of the area of human resources. The objectives were to identify strategies and policies in the area of human resources with the intensification of local contracts for international mobility; identify practices in the areas of human resources with respect to international mobility with local contract; and to compare, among the companies surveyed, the human resource practices of organizations that work with international mobility of the local contract type. In theoretical terms, the relevance of work in the life of individuals and the changes in the labor market are considered, which led professionals to rethink their jobs and careers, from the management of the career, which is mainly managed by the organizations to a self-directed model, with emphasis on protean careers and without frontiers. Another aspect concerns the differentiation of HR actions in an international context, where the area has the function of developing practices for the management of employees who work outside their country of origin. The development of global management makes it possible to understand a diversified environment and internationalization becomes a sine qua non for the survival of companies. In terms of methodological procedures this is a functionalist paradigm research, focused on the problem and focused on practical solutions. The approach is qualitative, of an applied nature, it is a multiple case study of descriptive and analytical objectives and the data were obtained through a semi-structured interview with the managers and analysts of the Human Resources area. Four professionals were interviewed, from organizations from different fields of activity. The analysis of the results showed similar practices between the HR areas of the companies surveyed and the strategic management of the people centralized in the matrix. The HRs of the subsidiaries are responsible for the operationalization of the international mobility processes with local contract and it is not done, by the HR of origin, the monitoring of the employee after the change to another country, the management of the people is in charge of the area in the country of destination of the auto started with local contract. This research has applicability with the proposal of more effective actions of the HRs of the subsidiaries before the local contract, through the reception and identification of the global professional and actions of incentive to the international career, with the realization of seminars, lectures or workshops and the creation of a unified database of interested employees with potential for international assignment, with a view to future hiring and development of training programs offered to these people.